Comparative Analysis Of Energy Industry Financial Performance Before, During Peak, And After The Covid-19 Pandemic - Odelia, Shanessa; Saner, Alvin Aerio; Tjusanto, Charice; Cecilia, Chelsea; Meivianna, Keisha; Amelia, Laura; Calliesta, Lienly; Saputro, Nicholle Christie (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to analyze significant differences in the financial ratios of energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2018 (pre-pandemic), 2021 (during the peak of the pandemic), and 2024 (post-pandemic). The analyzed ratios include liquidity (Quick Ratio/QR), solvency (Debt to Equity Ratio/DER), profitability (Return on Equity/ROE), and activity (Asset Turnover/ATO). The sample was purposively selected from companies with complete financial reports for all three periods. Using a quantitative approach and statistical tests (One Way ANOVA, Kruskal-Wallis, and Mann-Whitney), the results show a significant difference only in the liquidity ratio (QR), while DER, ROE, and ATO do not exhibit significant differences. These findings provide insight into the resilience of the energy sector during crises and offer valuable considerations for investors and policymakers.